Turbofan engine mathematic model for its static and dynamic characteristics research - Карпов, О.Є. (Proceedings of National Aviation University (archive), 2004)
Demands to mathematical model of the turbofan engine are determined in the article. The mathematical model is used for calculations static and dynamic parameters, which are required for estimation of engine technical state in operation. There are the mathematical model of the turbofan engine AИ-25 and the results of calculations static and dynamic parameters at initial condition in the article.